2017
DOI: 10.3389/fmed.2017.00020
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and Immunosenescence in the Elderly Patient: A Review

Abstract: Sepsis is a prevalent, serious medical condition with substantial mortality and a significant consumption of health-care resources. Its incidence has increased around 9% annually in general population over the last years and specially in aged patients group. Several risk factors such as comorbidities, preadmission status, malnutrition, frailty, and an impared function in the immune system called immunosenescence are involved in the higher predisposition to sepsis in the elderly patients. Immunosenescence statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 79 publications
0
96
0
2
Order By: Relevance
“…Higher rates of mortality in seasonal A /H3 may be the result of delayed oseltamivir therapy as well as aging and comorbidities that lead to immune dysfunction in addition to concomitant immunosenescence. [24][25][26] This study found that the presentation to the hospital of patients with severe influenza was significantly delayed compared with patients with mild influenza (mean, 3 days versus 1.6 days). This finding suggests that there are delays in the timely commencement of antiviral therapy in severe cases.…”
Section: Discussionmentioning
confidence: 74%
“…Higher rates of mortality in seasonal A /H3 may be the result of delayed oseltamivir therapy as well as aging and comorbidities that lead to immune dysfunction in addition to concomitant immunosenescence. [24][25][26] This study found that the presentation to the hospital of patients with severe influenza was significantly delayed compared with patients with mild influenza (mean, 3 days versus 1.6 days). This finding suggests that there are delays in the timely commencement of antiviral therapy in severe cases.…”
Section: Discussionmentioning
confidence: 74%
“…Based on 2016 National Report Sepsis 11 , sepsis can occur at various ages. According to a previous study conducted by Martin et al 12 patients with old age are more susceptible to infection due to decreased immunity factors, comorbidities, and malnutrition. Somatic mutations throughout a person's life will cause a decrease in cell regeneration capacity, cell repair, and immunity.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing emphasis is being placed on personalized medicine (Fig ), and an important aspect to consider is aging. Indeed, the links between immunosenescence and sepsis have been poorly investigated (Martín et al , ), although immunosenescence is associated with increased sensitivity of aged people to infection (Fulop et al , ; Mannick et al , ). However, most experimental sepsis models are performed on murine teenagers.…”
Section: Sepsis: a New Who Global Health Prioritymentioning
confidence: 99%